2021
DOI: 10.1111/hae.14388
|View full text |Cite
|
Sign up to set email alerts
|

Prostate interventions in patients with mild haemophilia: Safe and feasible

Abstract: Introduction:To date, there is no specific recommendation or evaluation of the morbidity of prostate surgery in patients with haemophilia (PWH) although this surgery is common and at high risk of bleeding. Aim:To assess the post-operative morbidity of benign prostate hyperplasia (BPH) surgeries and of oncological prostate interventions in patients with mild haemophilia A or B. Methods:We performed a monocentre, epidemiological, in real life study. Data were collected between 1 January, 1997 and 1 September, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The other two surgeries were a TURP and a laser vaporization, which are procedures described as causing increased bleeding, particularly when the scab falls off. 11 Again in these cases, tranexamic acid was not used, which would most likely limit this bleeding risk. Two of the cases of fair/poor efficacy seemed not to be related to the treatment or the hemophilia, since one bleed appeared while the FVIII level was normal (119 IU.dL À1 ) and the other was due to the removal of the gastrostomy tube by the patient himself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other two surgeries were a TURP and a laser vaporization, which are procedures described as causing increased bleeding, particularly when the scab falls off. 11 Again in these cases, tranexamic acid was not used, which would most likely limit this bleeding risk. Two of the cases of fair/poor efficacy seemed not to be related to the treatment or the hemophilia, since one bleed appeared while the FVIII level was normal (119 IU.dL À1 ) and the other was due to the removal of the gastrostomy tube by the patient himself.…”
Section: Discussionmentioning
confidence: 99%
“…Of these procedures, four were urological surgeries and tranexamic acid could not be used in two of those four procedures due to a contraindication related to coronary artery disease. The other two surgeries were a TURP and a laser vaporization, which are procedures described as causing increased bleeding, particularly when the scab falls off 11 . Again in these cases, tranexamic acid was not used, which would most likely limit this bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TURP is still regarded as the golden standard in the surgical treatment of BPH, but it is associated with higher complication rates compared to newer minimally invasive treatments (Rassweiler et al, 2006). In a recent study, TURP was associated with increased risk of bleeding in patients with HA, particularly after the patients have returned home (Mesnard et al, 2021). PAE is rapidly being established as a robust and safe alternative to surgery, especially in patients with larger prostates.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no guidelines for the management of patients with bleeding disorders, particularly those undergoing urological surgery. Few studies have reported the results of focused surgical procedures, such as transurethral prostate or bladder resection [6], bladder and prostate biopsies, and prostatectomy [7]. None of the studies included all patients who received care in the urology surgery department, regardless of the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%